Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Puskesmas Sidomulyo Pekanbaru - Widiantari '; Dewita Suryati Ningsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to determine how the variabel influence Leadership and Work Environment either simultan eously or partially on Employee Morale at Sidomulyo Health Center Pekanbaru. In this research use total sampling technic, where all of population to be a sample used. There are 51 people’s as a sample from the total people’s of population. The used analyze in this research is qualitative and quantitative with the make by SPSS program version 17. The results of this research idicate that the variabel of Leadership and Work Environment positive effect and significant on Employee Morale at Sidomulyo health center Pekanbaru. Leadership variable have an indirect effect on Employee Morale through Work Environment.Keywords: Leadership, Work Environment, and Employee Morale